Isolation, Identification Of Bromophenol Compound And Antibacterial Activity Of Kappaphycus SP - P. RAJASULOCHANA; P. KRISHNAMOORTHY; R. DHAMOTHARAN (International Journal of Pharma and Bio Sciences, 2012)
Extraction, isolation and partial purification of bromophenol compound in Kappaphycus sp. was carried out using TLC method. Antibacterial studies for specific bromophenol compound by disc diffusion method were conducted. Identification of a purified component was carried out by NMR technique. FTIRS and mass spectroscopy for elucidation of molecular structure of specific bromophenolic compound were done. From TLC studies, various bands were observed under UV light possessing the maximum value of RF 0.83 corresponding to RF1 band. The band was taken out and tested for antibacterial activity and detection of specific compound. Antimicrobial studies were carried out against various pathogens, Pseudomonas fluorescence, Staphylococcus aerus, Vibrio cholera, Proteus mirabilis and it was observed that the zone of inhibition for specific compound isolated from TLC was very prominent in case of Pseudomonas fluorescence and Staphylococcus aerus. C13 –NMR spectrum of Bromophenol derivative in CdCl3 showed eight Carbon signals. In mass spectrum analysis of Bromophenol compound, the compound was found to contain two Br atoms from the molecular ion peak at m/z 349.1676 and was analyzed for chemical formula C11 H9 O3 Br2. Based on the above characterization the compound was confirmed as-(E)-3-(2, 3-dibromo 4, 5-dihydroxyphenyl)-2-methyl-propenal.